FISCAL JUSTICE IN THE IMPLEMENTATION OF FINAL INCOME TAX FOR MSMES: A QUALITATIVE STUDY OF MICRO BUSINESS ACTORS IN THE POST-REGULATION PP NO. 55/2022 ERA - Muhammad Ardillah; Harti Budi Yanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The Government of Indonesia has implemented a tax policy in the form of Final Income Tax (PPh Final) for Micro, Small, and Medium Enterprises (MSMEs) as regulated in Government Regulation (PP) No. 55 of 2022. This policy aims to simplify tax administration and increase taxpayer compliance. However, the final rate system raises concerns regarding fiscal justice, particularly for micro-enterprises. This study uses a qualitative approach with in-depth interviews of micro-entrepreneurs in urban and rural areas to explore their perceptions of the fairness of the final income tax system. The findings show that many micro-businesses feel burdened by fixed tax rates despite declining income, which is perceived as unfair. The study concludes that the implementation of the final tax rate does not fully accommodate the real conditions of micro-enterprises, and further policy evaluation is required.